2020
DOI: 10.1016/j.cllc.2019.07.008
|View full text |Cite
|
Sign up to set email alerts
|

QTc Interval-Prolonging Medications Among Patients With Lung Cancer: Implications for Clinical Trial Eligibility and Clinical Care

Abstract: Background-Concomitant medication use, including agents that prolong the QTc interval, may exclude cancer patients from clinical trials. To estimate potential impact on accrual, we determined the prevalence of QTc-prolonging medication prescriptions in a national patient cohort.Methods-We identified adult patients in the Veterans Affairs system diagnosed with lung cancer 2003-2016. QTc-interval prolonging medications and risk category were obtained from CredibleMeds®. We calculated prevalence of prescriptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
3
1
1
Order By: Relevance
“…The variability in these results likely stems from the type of cancer populations that were studied and the duration of follow-up. The prevalence of prescriptions for ≥ 1 QT-prolonging drug in our cohort (99.6%) is higher than those found in past investigations, and this is likely due to the fact that we studied patients since their date of first cancer diagnosis (median duration of follow-up: 3.0 years), which was longer than study periods from past investigations that ranged from 1 week to 1 year ( 12 , 14 , 15 ).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The variability in these results likely stems from the type of cancer populations that were studied and the duration of follow-up. The prevalence of prescriptions for ≥ 1 QT-prolonging drug in our cohort (99.6%) is higher than those found in past investigations, and this is likely due to the fact that we studied patients since their date of first cancer diagnosis (median duration of follow-up: 3.0 years), which was longer than study periods from past investigations that ranged from 1 week to 1 year ( 12 , 14 , 15 ).…”
Section: Discussioncontrasting
confidence: 64%
“…Past studies have consistently found that prescriptions for QT-prolonging drugs are common in cancer patients and that numerous cancer therapeutics prolong QTc. With regard to the prevalence of prescriptions for QT-prolonging drugs, retrospective studies have found that 17.1% ( 15 ), 28.4% ( 14 ), and 92.6% ( 12 ) of cancer patients were prescribed ≥ 1 QT-prolonging drug as determined by CredibleMeds ® . The variability in these results likely stems from the type of cancer populations that were studied and the duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Some working group participants urged caution regarding concomitant medication-related eligibility (eg, drug-drug interactions, QTc prolongation risk) given the frequency and unclear clinical significance of these issues in clinical practice. 24,25…”
Section: Othermentioning
confidence: 99%
“…Examples considered by the group included reproductive status, autoimmune disease for immunotherapy, bleeding/clotting for antiangiogenic therapies, active infection for cytotoxic/immunosuppressive therapies, and drug-drug interactions. Some working group participants urged caution regarding concomitant medication-related eligibility (eg, drug-drug interactions, QTc prolongation risk) given the frequency and unclear clinical significance of these issues in clinical practice …”
Section: Recommendationsmentioning
confidence: 99%
“…Em 28,4% dos casos, houve prescrição de um medicamento prolongador do intervalo QT. Em 7,3% foram prescritos dois medicamentos simultâneos (105) . 0,7-40,7 milissegundos; p=0,047) (107) .…”
Section: Epidemiologia Das Interações Medicamentosas Prolongadoras Dounclassified